Variability of ferulenol and ferprenin concentration in French giant fennel (Ferula sp.) leaves. (July 2019) - Gault, Gilbert; Lefebvre, Sébastien; Benoit, Etienne; Lattard, Virginie; Grancher, Denis
Abstract: Few studies have reported quantitative data about the levels of prenylated coumarins in Ferula sp. Yet, the toxicity of Ferula sp. is only due to the presence of prenylated coumarins and to their concentrations and all studies suggest the existence of several chemotypes within the same species or even within the same variety. The aim of this study was to investigate the hypothesis of different chemotypes in french Ferula sp. in relationship with the botanical species. In this objective, the species of giant fennels and their concentrations in prenylated coumarins were explored. Three different species or subspecies of giant fennel were detected in continental France: F. communis communis communis L., F. communis catalaunica microcarpa Cauwet-Marc and F. glauca L. Surprisingly, the three species/subspecies of giant fennels were found to be located in exclusive and well separated geographical areas. In French giant fennels, ferulenol and ferprenin were detected. Distribution of ferulenol and ferprenin were found to be different between botanical varieties, but also according to the season, the soil and the altitude. Our study seems to suggest that among F. communis species, the same plant can be regarded as poisonous at one point and another as non-poisonous. Highlights: Ferula communis is the most widespread species of the genus in France. Ferulenol and ferprenin were detected in leaves of Ferula of France. Distribution of ferulenol and ferprenin is different between botanical varieties. Concentrations of prenylated coumarins are highly variable between plants. Season, soil and altitude seem to influence concentrations of prenylated coumarins.